Tolerant wideband high-efficiency grating coupler for TM mode excitation - Liow, Tsung-Yang (2013)
An optimized grating coupler featuring both ultra-broad bandwidth and high-efficiency has been achieved for the first time for the +1 diffraction order at a central operating wavelength 1.55 μm for TM polarization in horizontal slot waveguides. With proper design of the thickness of the groove thickness in grating region, we achieved a 60 nm 1 dB bandwidth, and the 3 dB bandwidth is 92 nm covering the entire C-band, and most of L-band and S-band. It is nearly two times more than the previously reported value. Maximum coupling efficiency of 65% has been achieved for positive detuned grating couplers with incident light from SMF at 8o. Sensitivity to fabrication and alignment tolerances of the structure has been analyzed.